SUKSESI DAN KINERJA KEUANGAN ATAS KEBERLANGSUNGAN PERUSAHAAN KELUARGA DI INDONESIA - NUNGKY BUDIARTI, ELIZA; VENUSITA, LINTANG (Jurnal Akuntansi AKUNESA, 2018)
Family business is a business that is usually derived from the founder or the previous generation to the next generation. But not many family business especially in Indonesia which thought and planned succession process. The continuation of the family business in the future is also uncertain. In addition, the family businesses performance also possible lower than non-family business, which are motivated by the chance of conflict on family business. By using descriptive qualitative method, with a conceptual approach. The results obtained indicate that the family business in Indonesia has a good financial performance because it is also supported by the motivation of the companys establishment. As well as the family business succession process in Indonesia have good planning from the previous generation and are supported with a good competence of the successor. So the continuation ofthe family company in Indonesia can take place with a long-term orientation. Keywords : family business, succession, financial performance